Defining Leadership in Smart Working Contexts: A Concept Synthesis - Iannotta, Michela; Meret, Chiara; Marchetti, Giorgia (Frontiers in Psychology, 2020)
This paper begins by considering the importance of leadership to pursue behavioral, cultural, technological, and ethical aspirations of smart working practices in order to develop a comprehensive understanding of leadership in smart working contexts. We adopt a literary approach to the concept synthesis method with which to critically analyze and conceptually map a wide set of related notions of leadership that are connected with the evolutive dynamics of smart working approaches. According to the scope conditions of the research, the role of leadership emerges with the purpose of changing behaviors, creating shared meanings, and integrating physical and technology-mediated interactions in smart working environments. With this in mind, the iterative integration of smart working and leadership literature has gradually begun to detect and classify the main characteristics of leadership in smart working contexts in terms of leadership antecedents, attributes, and outcomes. The interpretative synthesis results in an overarching conceptualization of “leading in smart working contexts” that depicts leadership as a naturally emerging phenomenon that combines agile logics and change management practices to align interests at different levels of the organization. These premises lead to the alleged “triple-win” configuration of smart working approaches. While encouraging in-depth discussion about the facilitative and performative function of leadership in smart working contexts, this study contributes to advancing knowledge on what “being a smart leader” actually means, and how to operatively apply this notion in smart working contexts. Together, the concept delineation and the operational definition of “smart leadership” offer important insights for both managerial action and future directions of research.